Polis democracy of the European Antiquity - Khankevich, Olga I. (Journal of the Belarusian State University. Law, 2021)
The author puts forward the idea of the communal nature of the Greek polis and Roman civitas (the main varieties of the polis state of European Antiquity), in which power and government were built on the basis of a communal model: council (senate), popular assembly (ecclesia, comitia), archons and magistrates in charge of current affairs. Full-fledged and equal members of the polis society, citizens (Greek polites, Latin cives), directly participated in government (direct democracy), approving laws by voting and electing members of magistrate colleges (the principle of popular sovereignty). The rights and interests of citizens were expressed and protected by the private (initially – civil) law, a number of achievements of which became, thanks to the Medieval codes, the property of modern civil law. The author’s method of developing the topic is based on the definitions, characteristics and conclusions of representatives of the political and legal theory of Antiquity and scientists of modern international schools of classical and Roman studies.
Keywords: republic; democracy; civil community; polis; civitas; civil law; citizen